Democratic Fundamentals in the Solomon Islands: Guadalcanal Provincial Assembly v The Speaker of National Parliament - Corrin Care, Jennifer (Victoria University of Wellington Law Review, 1997)
This article is a case note of Guadalcanal Provincial Assembly v The Speaker of National Parliament and the Minister for Provincial Government unreported, High Court, Solomon Islands, cc 309/96, 26 February 1997. The decision is a constitutional law case from the Solomon Islands filed by the applicant in response to the passing of the Provincial Government Act 1996. The author first introduces the political framework of the Solomon Islands, and then discusses the decision itself. The author then comments on the decision: first on the interpretation of the Constitution of the Solomon Islands, secondly on the role of Chiefs and Elders, and finally on the changes in the bench.